Synthesis and Antitubercular Activity of New L-serinyl Hydrazone Derivatives - Campbell Pinheiro, Alessandra; Roland Kaiser, Carlos; Cristina Mendonca Nogueira, Thais; Aquino Carvalho, Samir; Ferreira da Silva, Edson; de Oliveira Feitosa, Larisse; das Gracas Muller de Oliveira Henriques, Maria; Luis Peixoto Candea, Andre; Cristina Silva Lourenco, Maria; Vinicius Nora de Souza, Marcus (Medicinal Chemistry, 2011)
A series of 32 L-serinyl hydrazone derivatives have been synthesized and evaluated for their in vitro antibacterial activity against Mycobacterium tuberculosis H37Rv, being also evaluated their cell viabilities in non infected and infected macrophages with Mycobacterium bovis Bacillus Calmette-Guerin (BCG). The compounds 8c, 8e, 8h and 8i, were non-cytotoxic and exhibited an important minimum inhibitory concentration (MIC) activity between 25 and 100μg/mL, which can be compared with that of the tuberculostatic drug D-cicloserine (5-20μg/mL).
Keywords: isoniazid and rifampin